A modified laboratory approach to determine reaeration rate for river water - ., Md Nuruzzaman; Al-Mamun, Abdullah; Salleh, Md Noor (Springer Berlin Heidelberg, 2018)
It is reported that reaeration rates determined from laboratory investigation may not suit well in predicting reaeration rate of natural streams. Sampling method during reaeration experiment is a potential source of error in laboratory estimation of reaeration rate coefficient for river waters, which has been addressed in this research. A modified method based on sampling procedure in a flume was adopted to develop a reaeration rate equation for Pusu River in Malaysia,which is demographically a very important river. An important feature including several culverts along the course of the river was also considered to model dissolved oxygen (DO) concentration.DOwas calibrated and validated using water quality analysis simulation program (WASP) considering appropriate kinetic rate coefficients for Pusu River. Performance of the new reaeration rate equation and other process equations in the calibration and validation data was assessed in terms of root-mean-square error (RMSE), mean error between observed and predicted data and R2 value. Study results revealed that the equation developed in B Abdullah Al-Mamun mamun@iium.edu.my Md Nuruzzaman suvo.ruet@gmail.com http://waterzaman.weebly.com/ Md Noor Bin Salleh mdnoor@iium.edu.my 1 Department of Civil Engineering, Rangpur Engineering College, Rangpur 5403, Bangladesh 2 Department of Civil Engineering, Kulliyyah of Engineering, International Islamic University Malaysia (IIUM), 53100 Kuala Lumpur, Malaysia 3 Bioenvironmental Engineering Research Center (BERC), Kulliyyah of Engineering, International Islamic University Malaysia (IIUM), 53100 Kuala Lumpur, Malaysia this research considering the impact of culverts on reaeration rate predicted DO in Pusu River with improved accuracy as compared to the other equations. RMSEs were found to be 0.083 and 0.067 mg/L for calibration and validation data, respectively. Mean errors of observed and model-predicted data were 0.06 and 0.05 mg/L for calibration and validation,respectively. The R2 value was 0.99 in both cases. The study results facilitate accuracy in future studies on DO of Pusu River.